Determination of target xenobiotics and unknown compound residues in food, environmental, and biological samples - Tuzimski, Tomasz; Sherma, Joseph (Boca Raton, FL : CRC Press, 2018)
"Xenobiotics are chemical compounds foreign to a given biological system. In animals and humans, xenobiotics include drugs, drug metabolites, and environmental pollutants. In the environment, xenobiotics include synthetic pesticides, herbicides, and industrial pollutants. Many techniques are used in xenobiotics residue analysis; the method selected depends on the complexity of the sample, the nature of the matrix/analytes, and the analytical techniques available. This reference will help the analyst develop effective and validated analytical strategies for the analysis of hundreds of different xenobiotics on hundreds of different sample types, quickly, accurately and at acceptable cost"--
Overview of the field of chromatographic methods of xenobiotics residue analysis and organization of the book / Tomasz Tuzimski, Joseph Sherma -- Xenobiotics : main groups, possible classifications and properties / Tomasz Tuzimski, Joseph Sherma -- Choice of the mode of analytical (chromatographic) method for analysis of xenobiotics and unknown compounds on the basis of the properties of analytes / Michal Markuszewski, Marta Kordalewska -- New trends in sample preparation method for xenobiotcs residues analysis -- QuEChERS / Tomasz Tuzimski -- High resolution mass spectrometry (tandem mass spectrometry) -- new trends and limitations in analysis of xenobiotics and unknown compounds in food, environmental and biological samples / Lukasz Ciesla -- Other analytical methods : new trends and limitations to analysis of xenobiotics and unknown compounds residues in food, environmental and biological samples / Tomasz Tuzimski -- HPLC-MS(MS/MS) as a method of identification and quantification of drugs and veterinary drugs residues in food, environmental and biological samples / Tomasz Tuzimski -- Ultra-performance liquid chromatography (UPLC) applied to analysis of drugs and veterinary drugs residues in food, environmental and biological samples / Tomasz Tuzimski -- Gas chromatography (GC) applied to analysis of drugs and veterinary drugs residues in food, environmental and biological samples / Piotr Stepnowski -- HPLC-MS(MS/MS) as a method of identification and quantification of vitamins in food, environmental and biological samples / Anna Petruczynik -- Ultra-performance liquid chromatography (UPLC) applied to analysis of vitamins in food, environmental and biological samples / Anna Petruczynik -- HPLC-MS(MS/MS) as a method of identification and quantification of dyes in food, environmental and biological samples / Anna Petruczynik -- Ultra-performance liquid chromatography (UPLC) applied to analysis of dyes in food, environmental and biological samples / Anna Petruczynik -- HPLC-MS(MS/MS) as a method of identification and quantification of mycotoxins in food, environmental and biological samples / Anna Petruczynik, Tomasz Tuzimski -- Ultra-performance liquid chromatography (UPLC) applied to analysis of mycotoxins in food, environmental and biological samples / Anna Petruczynik, Tomasz Tuzimski -- HPLC-MS(MS/MS) as a method of identification and quantification of environmental bioindicators residues in food, environmental and biological samples / Wojciech Piekoszewski -- Ultra-performance liquid chromatography (UPLC) applied to analysis of environmental bioindicators residues in food, environmental and biological samples / Wojciech Piekoszewski -- Gas chromatography (GC) applied to analysis of environmental bioindicators residues in food, environmental and biological samples / Wojciech Piekoszewski -- Multidimensional chromatography applied to analysis of xenobiotics and unknown compounds in food, environmental and biological samples / Haleigh Boswell, Tadeusz Górecki -- Quo vadis of analysis of xenobiotics and unknown compounds in food, environmental and biological samples / Tomasz Tuzimski, Joseph Sherma.
OCLC-licensed vendor bibliographic record.
Keywords: Xenobiotics -- Analysis; MEDICAL / Pharmacology